THE GROUPING OF VILLAGES ON KB SUPPORTING INDICATORS AS A BASIC MAPPING FOR FORMATION KAMPUNG KB IN SURABAYA - Erma Oktania Permatasari; Wahyu Wibowo; Budi Priyono (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2021)
Population problems in Indonesia is still important and complex issues that must be resolved. Indonesia has the fourth largest population after China, India and the United States. Uncontrolled population growth will cause problems, such as lack of employment opportunity, unemployment and increased crime. To solve these problems, the government through BKKBN (The National Population and Family Planning) increase the promotion of Family Planning (KB) with the slogan